Visualizing leukocyte trafficking in the living brain with 2-photon intravital microscopy - Pai, Saparna; Danne, Karyn J.; Qin, Jim; Cavanagh, Lois L.; Smith, Adrian; Hickey, Michael J.; Weninger, Wolfgang (Frontiers in Cellular Neuroscience, 2013)
Intravital imaging of the superficial brain tissue in mice represents a powerful tool for the dissection of the cellular and molecular cues underlying inflammatory and infectious central nervous system diseases. We present here a step-by-step protocol that will enable a non-specialist to set up a two-photon brain-imaging model. The protocol offers a two-part approach that is specifically optimised for imaging leukocytes but can be easily adapted to answer varied CNS-related biological questions. The protocol enables simultaneous visualization of fluorescently labelled immune cells, the pial microvasculature and extracellular structures such as collagen fibres at high spatial and temporal resolution. Intracranial structures are exposed through a cranial window, and physiologic conditions are maintained during extended imaging sessions via continuous superfusion of the brain surface with artificial cerebrospinal fluid. Experiments typically require 1-2 hours of preparation, which is followed by variable periods of immune cell tracking. Our methodology converges the experience of two laboratories over the past 10 years in diseased animal models such as cerebral ischemia, lupus, cerebral malaria and toxoplasmosis. We exemplify the utility of this protocol by tracking leukocytes in transgenic mice in the pial vessels under steady-state conditions.